Open access and health librarians in 2011 - Devon Greyson (Journal of the Canadian Health Libraries Association, 2014)
This paper provides an overview of the open access (OA) movement to date, with specific focus on both health information and Canada, updates on some major areas of OA activity, and a discussion of emerging opportunities and needs for librarians due to the evolving OA paradigm.